Bilateral Transcranial Magnetic Stimulation on DLPFC Changes Resting State Networks and Cognitive Function in Patients With Bipolar Depression - Kazemi, Reza; Rostami, Reza; Khomami, Sanaz; Baghdadi, Golnaz; Rezaei, Mehdi; Hata, Masahiro; Aoki, Yasunori; Ishii, Ryouhei; Iwase, Masao; Fitzgerald, Paul B. (Frontiers in Human Neuroscience, 2018)
Introduction: Bipolar patients have abnormalities in cognitive functions and emotional processing. Two resting state networks (RSN), the default mode network (DMN) and the Sensorimotor network (SMN), play a decisive role in these two functions. Dorsolateral prefrontal cortex (DLPFC) is one of the main areas in the Central Executive Network (CEN), which is linked to the activities of each of the two networks. Studies have found DLPFC abnormalities in both hemispheres of patients with bipolar depression. We hypothesized that the bilateral repetitive transcranial magnetic stimulation (rTMS) of DLPFC would produce changes in the activity of both the SMN and DMN as well as relevant cognitive function in patients with bipolar depression that responded to treatment. Methods: 20 patients with bipolar depression underwent 10 sessions of 1 Hz rTMS on right DLPFC with subsequent 10 Hz rTMS on left DLPFC. Changes in EEG resting networks between pre and post rTMS were evaluated utilizing low-resolution electromagnetic tomography (eLORETA). Depression symptom was assessed using the Beck Depression Inventory (BDI-II) and cognitive function was assessed by Verbal Fluency Test (VFT), Rey Auditory Verbal Test (RAVLT), Stroop Test, and Wisconsin Card Sorting Test (WCST). Results: Responders to rTMS showed significantly lower DMN activity at baseline and a significant decrease in SMN connectivity after treatment. Non-responders didn’t significantly differ from the control group at the baseline and they showed higher activity in the SMN, visual network and visual perception network compared to control group following treatment. Bilateral rTMS resulted in significant changes in the executive functions, verbal memory, and depression symptoms. No significant changes were observed in selective attention and verbal fluency. Conclusion: Bilateral stimulation of DLPFC, as the main node of CEN, results in changes in the activity of the SMN and consequently improves verbal memory and executive functions in patients with bipolar depression.